2013
DOI: 10.4062/biomolther.2012.075
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Epigallocatechin-3-Gallate on Microsomal Cyclooxygenase-1 Activity in Platelets

Abstract: In this study, we investigated the effect of (–)-epigallocatechin-3-gallate (EGCG), a major component of green tea catechins from green tea leaves, on activities of cyclooxygenase (COX)-1 and thromboxane synthase (TXAS), thromboxane A2 (TXA2) production associated microsomal enzymes. EGCG inhibited COX-1 activity to 96.9%, and TXAS activity to 20% in platelet microsomal fraction having cytochrome c reductase (an endoplasmic reticulum marker enzyme) activity and expressing COX-1 (70 kDa) and TXAS (58 kDa) prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…Regarding the reported inhibition of COX‐1 activity in platelets (Lee et al , ; Table ), this effect is not supported by the results of a human study conducted by Hirano‐Ohmori et al (). After the consumption of seven cups of GT a day for 2 weeks by healthy subjects, no significant changes in the aggregation of platelets were observed, despite a significant decrease in the serum low density lipoproteins (MDA‐LDL).…”
Section: Enzymatic Inhibitionmentioning
confidence: 86%
“…Regarding the reported inhibition of COX‐1 activity in platelets (Lee et al , ; Table ), this effect is not supported by the results of a human study conducted by Hirano‐Ohmori et al (). After the consumption of seven cups of GT a day for 2 weeks by healthy subjects, no significant changes in the aggregation of platelets were observed, despite a significant decrease in the serum low density lipoproteins (MDA‐LDL).…”
Section: Enzymatic Inhibitionmentioning
confidence: 86%
“…Many of the studies on platelet aggregation have been carried out using various animal platelets. In addition to showing that green tea catechins were involved in inhibition of platelet aggregation, studies suggested that catechins may affect several cellular targets that are related to platelet activation, including: through the arachadonic acid pathway, inhibition of a cytoplasmic increase in calcium, decreased thrombaxane A 2 (TXA 2 ) production, and inhibition of cyclooxygenase-1 (COX)-1 [90][91][92][93]. A study using human platelets concluded that EGCG was able to inhibit platelet activation by adenosine diphosphate (ADP) stimulation, and suppressed the p38 MAPK phosphorylation of heat shock protein 27 (HSP27), which would inhibit the release of pro-thrombotic contents from platelets [94].…”
Section: Platelet Aggregationmentioning
confidence: 99%
“…In a previous study, we reported that chlorogenic acid (50 μM), an analogue of CAFA, inhibits the COX-1 activity in platelets to 69.7% compared with that observed (52.5±2.5 pmoL/ min/protein-mg) in the controls in vitro 36) . In addition, the COX-1 inhibitor aspirin (50 μM) inhibited the COX-1 activity in platelets to 11.3% compared with that observed (1.59 nmoL/min/protein-mg) in the controls in vitro 12) . An autacoidal molecule, TXA2, produces IP3 to mobilize [Ca 2+ ]i via the G-protein coupled receptor/PLC-β pathway to constrict the vessel tract 7,8,35,[37][38][39] , which enforces thrombus formation.…”
Section: mentioning
confidence: 70%
“…A polyphenolic compound, (-)-epigallocatechin-3-gallate (EGCG), in green tea is known to produce cAMP via adenylate cyclase activation and subsequently phosphorylate vasodilator-stimulated phosphoprotein (VASP)-Ser 157 via A-kinase activation to inhibit [Ca 2+ ]i mobilization and TXA2 production on collageninduced platelet aggregation 11) . The inhibition of TXA2 production by EGCG is involved in the inhibition of COX-1 12) . With regard to the effects of a phenolic compound, caffeic acid (CAFA, Fig.…”
Section: Methodsmentioning
confidence: 99%